Optimization of a rat lumbar IVD degeneration model for low back pain. Issue 2 (22nd June 2020) - Glaeser, Juliane D.; Tawackoli, Wafa; Ju, Derek G.; Yang, Jae H.; Kanim, Linda EA; Salehi, Khosrowdad; Yu, Victoria; Saidara, Evan; Vit, Jean‐Phillipe; Khnkoyan, Zhanna; NaPier, Zachary; Stone, Laura S.; et al.
Abstract: Introduction: Intervertebral disc (IVD) degeneration is often associated with low back pain and radiating leg pain. The purpose of this study is to develop a reproducible and standardized preclinical model of painful lumbar IVD degeneration by evaluation of structural and behavioral changes in response to IVD injury with increasing needle sizes. This model can be used to develop new therapies for IVD degeneration. Methods: Forty‐five female Sprague Dawley rats underwent anterior lumbar disc needle puncture at levels L4‐5 and L5‐6 under fluoroscopic guidance. Animals were randomly assigned to four different experimental groups: needle sizes of 18 Gauge (G), 21G, 23G, and sham control. To monitor the progression of IVD degeneration and pain, the following methods were employed: μMRI, qRT‐PCR, histology, and biobehavioral analysis. Results: T1‐ and T2‐weighted μMRI analysis showed a correlation between the degree of IVD degeneration and needle diameter, with the most severe degeneration in the 18G group. mRNA expression of markers for IVD degeneration markers were dysregulated in the 18G and 21G groups, while pro‐nociceptive markers were increased in the 18G group only. Hematoxylin and Eosin (H&E) and Alcian Blue/Picrosirius Red staining confirmed the most pronounced IVD degeneration in the 18G group. Randall‐Selitto and von Frey tests showed increased hindpaw sensitivity in the 18G group. Conclusion: Our findings demonstrate that anterior disc injury with an 18G needle creates severe IVD degeneration and mechanical hypersensitivity, while the 21G needle results in moderate degeneration with no increased pain sensitivity. Therefore, needle sizes should be selected depending on the desired phenotype for the pre‐clinical model. Abstract : Study Design Overview This study establishes and validates a rat model for lumbar IVD degeneration that is reflected in painful behavior. Based on our findings we conclude that annular disc injury with a 18G needle creates severe, painful IVD degeneration, while 21G needle injury results in moderate degeneration.